Exceptional poles of local L-functions for GSp(4) with respect to split Bessel models - Weissauer, Rainer (Journal of number theory, 2023)
This paper deals with the local nonarchimedean L-factors of the Piateskii-Shapiro L-series for automorphic representations of the group GSp(4). The local factors may have exceptional poles that a priori depend on the choice of a Bessel model. We compute the exceptional local L-factors for split Bessel models and show their independence from the choice of the Bessel model. This complements previous results on the regular part of these L-factors.
Online veröffentlicht am 25. Juli 2022, Dateiversion vom 27. Oktober 2022
Gesehen am 31.01.2023